The impact of a named GP scheme on continuity of care and emergency hospital admission: a cohort study among older patients in England, 2012–2016. Issue 9 (23rd September 2019) - Tammes, Peter; Payne, Rupert A; Salisbury, Chris; Chalder, Melanie; Purdy, Sarah; Morris, Richard W
Abstract : Objective: To investigate whether the introduction of a named general practitioner (GP, family physician) improved patients' healthcare for patients aged 75 and over in England. Setting: Random sample of 27 500 patients aged 65 to 84 in 2012 within 139 English practices from the Clinical Practice Research Datalink linked with Hospital Episode Statistics. Design: Prospective cohort approach, measuring patients' GP consultations and emergency hospital admissions 2 years before/after the intervention. Patients were grouped in (i) aged over 74 and (ii) younger than 75 in both periods in order to compare who were or were not subject to the intervention. Adjusted associations between the named GP scheme, continuity of care and emergency hospital admission were examined using multilevel modelling. Intervention: National Health Service policy to introduce a named accountable GP for patients aged over 74 in April 2014. Main outcome measures: (A) Continuity of care index-score, (B) risk of emergency hospital admissions, (C) number of emergency hospital admissions. Results: The intervention was associated with a decrease in continuity index-scores of −0.024 (95% CI −0.030 to −0.018, p<0.001); there were no differences in the decrease between the two age groups (−0.005, 95% CI −0.014 to 0.005). In the pre-intervention and post-intervention periods, respectively, 15.4% and 19.4% patients had an emergency admission. The probability of an emergency hospital admission increased after the intervention (OR 1.156, 95% CI 1.064 to 1.257, p=0.001); this increase was bigger for patients over 74 (relative OR 1.191, 95% CI 1.066 to 1.330, p=0.002). The average number of emergency hospital admissions increased after the intervention (rate ratio (RR) 1.178, 95% CI 1.103 to 1.259, p<0.001); this increase was greater for patients over 74 (relative RR 1.143, 95% CI 1.052 to 1.242, p=0.001). Conclusion: The introduction of the named GP scheme was not associated with improvements in either continuity of care or rates of unplanned hospitalisation.